Progress and challenges in melanoma immunotherapy - LIN Jing; CHEN Yaying; CHEN Yu (Pifu-xingbing zhenliaoxue zazhi)
Melanoma is highly invasive and has a high mortality rate. The effectiveness of traditional treatment methods is limited. Immunotherapy based on immune checkpoint inhibitors has achieved a major breakthrough in melanoma treatment. Among them, classic immune checkpoint inhibitors, such as CTLA-4, PD-1/PD-L1, have a landmark significance in the field of immuno-oncology. Meanwhile, emerging checkpoint inhibitors, including LAG-3, TIM-3, and TIGIT, have demonstrated promising new therapeutic effects. Significant progress has also been made in cellular therapies and neoantigen-based vaccines. Currently, immunotherapy combination regimens significantly enhance the therapeutic effect through the synergistic action of multiple mechanisms, but they also face challenges such as immune-related adverse reactions and immune resistance. Future research directions lie in exploring novel combined targets, integrating cutting-edge technologies, developing personalized treatment plans, and implementing strategies such as resistance monitoring, to overcome current therapeutic limitations. This article systematically summarizes the latest progress and existing challenges in the immunotherapy of melanoma, aiming to provide new insights and references for clinical practice and scientific research.